Primary Sarcoma of the Specialised Prostatic Stroma: A Case Report and Review of the Literature - Rosanna Zamparese; Francesco Corini; Antonio Braccischi; Antonella D'Angelo; Lucilla Diamanti; Marina Del Vecchio; Willy Giannubilo; Vladimiro Mambelli (Case Reports in Pathology)
Primary sarcoma tumours of the prostate are rare and are classified, according to their histology, as stromal tumours of uncertain malignant potential (STUMP) and stromal prostatic sarcoma (PS; low and high grade). We describe a case of a 71-year-old man that developed progressive urinary obstruction symptoms and was subjected to a transurethral prostatic resection (TURP). Histologically, there is a diffuse proliferation of epithelioid and spindle cells that showed rare atypical mitotic figures. Immunohistochemically, the neoplastic cells express diffusely CD34 and focally progesterone whereas no immunoreactivity was seen for cytocheratin, desmin, S-100, Bcl-2, chromogranin, CD117, and actin smooth muscle. A final diagnosis of low-grade prostatic stromal sarcoma (LG-PS) was made. This is a really rare neoplasm; in the literature, in fact, to our knowledge, only 6 cases are described and all of these were alive and free of disease at followup. Our patient too is free of disease at 15 months from the diagnosis.